(untitled) (Innovative Technologica: Methodical Research Journal, 2021)
This article reflects the effective principles of improving product quality and its competitiveness by improving the quality management system of enterprises. Based on the principle of competitiveness, the reduction of the volume of substandard and non-compliant products of the manufacturer is taken into account.